Analyzing Construction Risk Factors in Large-Scale Projects: Case Study on the Suramadu Bridge - Reinaldy Jastino; Indrastuti (Fakultas Teknik Sipil dan Perencanaan, 2024)
This study aims to comprehensively examine the risk management practices, challenges, and strategies employed during the construction of the Suramadu Bridge. A structured data collection process began with defining clear objectives to identify risks related to structural integrity, environmental impacts, financial uncertainties, project delays, and safety concerns. Key search terms such as